Neutral polyfluoroalkyl substances in the atmosphere over the northern South China Sea. (July 2016) - Lai, Senchao; Song, Junwei; Song, Tianli; Huang, Zhijiong; Zhang, Yingyi; Zhao, Yan; Liu, Guicheng; Zheng, Junyu; Mi, Wenying; Tang, Jianhui; Zou, Shichun; Ebinghaus, Ralf; et al.
Abstract: Neutral Polyfluoroalkyl substances (PFASs) in the atmosphere were measured during a cruise campaign over the northern South China Sea (SCS) from September to October 2013. Four groups of PFASs, i.e., fluorotelomer alcohols (FTOHs), fluorotelomer acrylates (FTAs), fluorooctane sulfonamides (FOSAs) and fluorooctane sulfonamidoethanols (FASEs), were detected in gas samples. FTOHs was the predominant PFAS group, accounting for 95.2–99.3% of total PFASs (Σ PFASs), while the other PFASs accounted for a small fraction ofΣ PFASs. The concentrations ofΣ PFASs ranged from 18.0 to 109.9 pg m −3 with an average of 54.5 pg m −3 . The concentrations are comparable to those reported in other marine atmosphere. Higher concentrations ofΣ PFASs were observed in the continental-influenced samples than those in other samples, pointing to the substantial contribution of anthropogenic sources. Long-range transport is suggested to be a major pathway for introducing gaseous PFASs into the atmosphere over the northern SCS. In order to further understand the fate of gaseous PFASs during transport, the atmospheric decay of neutral PFASs under the influence of reaction with OH radicals and atmospheric physical processes were estimated. Concentrations of 8:2 FTOH, 6:2 FTOH and MeFBSE from selected source region to the atmosphere over the SCS after long-range transport were predicted and compared with the observed concentrations. It suggests that the reaction with OH radicals may play an important role in the atmospheric decay of PFAS during long-range transport, especially for shorted-lived species. Moreover, the influence of atmospheric physical processes on the decay of PFAS should be further considered. Graphical abstract: Highlights: Neutral PFASs were detected in the atmosphere over the northern South China Sea. FTOH was the predominant PFAS group measured in gas phase samples. Atmospheric transport is the major pathway for neutral PFASs to oceanic area. Reaction with OH radicals is an important decay route for short-lived PFAS. Abstract : Characteristics and atmospheric decay of neutral PFASs has been studied in the northern South China Sea.